Green synthesis of bimetallic CuO@NiO nanocomposite for the removal of glyphosate - BOONSERM, Kornkanok; SUTCHA, Anan; PHINJAROENPHAN, Rarm (Journal of Metals, Materials and Minerals, 2024)
Green synthesis of photocatalyst bimetallic CuO@NiO nanocomposite for eliminating organic hazardous glyphosate (Gly) solution has been introduced. The nanocomposite has been successfully developed from mango (Mangifera indica L.) peel extracted solution by a simultaneous reduction process. HRTEM, XRD, and EDX have also been used to explore the nanostructure, crystal conformation, and chemical compositions of CuO@NiO. Using UV-vis spectrometer, we have observed the photo-catalytic activity and kinetic removal rate constant of CuO@NiO in terms of glyphosate elimination under UV light illumination. Compared with pure CuO and NiO nanoparticles, CuO@NiO displayed improved and enhanced photocatalytic activity. This work demonstrates an eco-friendly, low-cost material with high efficiency for removing Gly, which has applications in environmental protection.